The State of Islam : Culture and Cold War Politics in Pakistan - Saadia Toor (London Pluto Press, 2011)
Studies Pakistan through the lens of the Cold War and the War on Terror and sheds light on the processes behind the rise of militant Islam.
Include Note, Reference and Index
Keywords: Pakistan -- Cold War (1945-1989) -- Islam and politics -- Politics and government